Russian and Foreign Parliamentarism as Viewed by Contemporary Researchers - Evgenii S. Dobrovol'skii (Historia provinciae: журнал региональной истории, 2023)
The review analyzes the collection of papers of the Fifteenth International Scientific Conference “Current Problems of Parliamentarism: History and Modernity” (Tauride Readings 2021), held in St Petersburg in December 2021. The reviewer examines the problems and topics of the articles included in the collection as well as the issues put forward during the discussions and the round table. The analysis of various aspects of the activities of the State Duma in the early 20th century takes the central place in most studies. Special attention is paid to the materials devoted to parliamentarism in foreign countries (Great Britain, China, Croatia, and Germany).